Development of control system for quadrotor unmanned aerial vehicle using LoRa wireless and GPS tracking - Teddy Surya Gunawan; Wan Athereah Yahya; Erwin Sulaemen; Mira Kartiwi; Zuriati Janin (Universitas Ahmad Dahlan, 2020)
In the past decades, there has been a growing interest in unmanned aerial vehicles (UAVs) for educational, research, business, and military purposes. The most critical data for a flight system is the telemetry data from the GPS and wireless transmitter and also from the gyroscope and accelerometer. The objective of this paper is to develop a control system for UAV using long-range wireless communication and GPS. First, Matlab simulation was conducted to obtain an optimum PID gains controller. Then LoRa wireless was evaluated during clear and rainy days. Static and dynamic points measurement was conducted to validate and optimize GPS accuracy. GeoMapping in Matlab and Google GPS GeoPlanner were then used to analyze the traveled UAV flight path.